ChemInform Abstract: Practical Organocatalytic Synthesis of Functionalized Non‐C2‐Symmetrical Atropisomeric Biaryls. Issue 20 (April 2016) - Gao, Hongyin; Xu, Qing‐Long; Keene, Craig; Yousufuddin, Muhammed; Ess, Daniel H.; Kuerti, Laszlo
Abstract: Acid catalyzed coupling of electron rich p‐benzoquinone mono‐acetals and their corresponding mono‐acetal mono‐imines with reactive phenols offers a direct access to unsymmetrical biaryls.